IMPROVING THE HARD SKILLS AND SOFT SKILLS OF MADRASAH TEACHERS FOR DEALING ASEAN ECONOMIC COMMUNITY (AEC) - Mahmudah, Laely (ADDIN, 2016)
ASEAN Economic Community (AEC) has been started rolling. Market competition, industry, and skilled workers, especially in the field of education are becoming increasingly stringent. Madrasah teachers as the front liners in the education process should improve the quality of human resources. Hard skills and soft skills of madrasah teachers must be improved to deal with the Asean Economic Community (AEC). Hard skills are academic skills that include pedagogic competence and professional competence. How to improve the hard skills is to meet the pedagogic competence (ability to manage learning students) and professional competence (the ability to master the learning material is broad and deep). Soft skills is the ability to organize themselves (intrapersonal skills, such as creativity, motivation, and self-contained) and the ability to interact with others (interpersonal skills, such as communication, team building and adaptation) to maximize performance. Soft skills include personal competence and social competence. Madrasah teachers should be able to change the mindset of a passenger became good driver. Professional madrasah teachers are teachers who have the balanced hard skills and soft skills, which can compete healthily in AEC era.